Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2147/copd.s165857
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of nasal budesonide treatment on COPD patients with coexistent rhinitis

Abstract: BackgroundA high percentage of patients with COPD report chronic nasal symptoms. The study aims to evaluate the clinical impact of a 2-month treatment with inhaled nasal budesonide (100 µg per nostril twice daily) in patients affected by COPD with chronic rhinitis comorbidity.Patients and methodsFifty-three stable COPD patients in therapy according to the Global initiative for chronic Obstructive Lung Disease recommendations were enrolled; 49 completed the study. At enrollment (visit 0), patients underwent ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…An observational study from 2018 treated a cohort of 49 COPD patients with 8 weeks of nasal budesonide. They found that not only did the UAS decline substantially, but COPD symptom burden score such as CAT score and dyspnoea score (mMRC) diminished as well [ 36 ]. This study however was neither randomised nor placebo-controlled.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study from 2018 treated a cohort of 49 COPD patients with 8 weeks of nasal budesonide. They found that not only did the UAS decline substantially, but COPD symptom burden score such as CAT score and dyspnoea score (mMRC) diminished as well [ 36 ]. This study however was neither randomised nor placebo-controlled.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been reported to be the strongest predictor of all-cause mortality in a prospective cohort study of COPD patients. 45 Improvement in the grade of dyspnea after 8 weeks of nasal corticosteroid therapy in a pilot study of COPD patients 42 is a promising result that requires confirmation in a larger study.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Moreover, nasal symptoms (SNOT items 1–8), degree of dyspnea (mMRC) and HRQoL (CAT score) were significantly improved after 8 weeks of daily anti-inflammatory treatment with nasal budesonide in a recent clinical trial in stable COPD patients. 42 Thus, clinicians should be aware of the high prevalence of sinonasal symptoms in COPD, and enquiry about their presence in these patients should be a routine in clinical practice. Early recognition and treatment of sinonasal symptoms may contribute to optimising the management of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Intranasal administration of ICS improves nasal symptoms score but also the COPD assessment test score and decreases dyspnea, quantified according to the modified Medical Research Council (mMRC) scale (83).…”
Section: Accepted Manuscriptmentioning
confidence: 99%